Термодинамічний аналіз квантових обчислень - Білоколос, Є.Д.; Теслик, М.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The entropy dynamics of register qubits under interaction while processing any many-qubit gate has been considered. These results are applied to the estimation of the amounts of generated entropy and energy dissipation for two- and three-qubit gates, which allows us to calculate their contribution to the “price” of both processing any quantum algorithm and reading a result while measuring the register’s state.